(untitled) (Research, Society and Development, 2022)
Introduction: With the growing increase in corn production in all Brazilian regions, researchers are increasingly looking for techniques that seek to evidence and control the occurrence of pathogens commonly found in this crop, among which is Fusarium spp. Objective: To carry out a literature review on the transmissibility of Fusarium in maize seeds at different exposure times. Methodology: Systematic exploratory literature review. The research was carried out from August to November 2022. For the writing, a bibliographic survey was carried out on the following platforms: Portal de Periódicos Capes, Google academic, Scielo, Research Gate, Elsevier and PubMed. Final Considerations: Fusarium spp. is a type of fungus that attacks corn seeds, causing diseases that end up harming the crop’s production. In this work, it was verified that the transmissibility of Fusarium in corn seeds was verified from the exposure of the seeds for a minimum period of 16 hours.